Bemisia tabaci (Hemiptera: Aleyrodidae) Species Complex From Cotton Cultivars: A Comparative Study of Population Density, Morphology, and Molecular Variations. (1st March 2014) - Thomas, Asha; Kar, Anand; Rebijith, K. B.; Asokan, R.; Ramamurthy, V. V.
Abstract: Morphological and molecular variations of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) on cotton cultivars having varying trichome density were evaluated at New Delhi, India. The study evaluates the role of host plant nature on puparia and putative species groups of the B. tabaci species complex. More specifically, the study was done to explore the host plant characters and their effect on the population density, morphology of the puparia, and to identify the putative species groups of the B. tabaci species complex occurring on cotton. Population density was observed to be higher in cultivars with less trichome density. Studies on the puparia showed statistically significant variations on different cotton cultivars ( P ≤ 0.01), which was supported by scattergraphs derived from principal components and canonical discriminant analysis. Statistical analysis revealed the influence of trichome density on population density of B. tabaci . Sequence analyses using mitochondrial cyctochrome oxidase I confirmed the presence of three putative species Asia 1, Asia II 1, and Asia II 7 on the cultivars of cotton. The current study revealed that genetic variation is not influenced the variations in the trichome density and morphological variation.